Cybersecurity in the humanitarian sector: new challenges and solutions - Chen, Christopher Zhiming (2023)
On 3 November 2022, the International Committee of the Red Cross released its report, “Digitalising the Red Cross, Red Crescent and Red Crystal Emblems: Benefits, Risks and Possible Solutions.” It was in response to cyber intrusions the movement faces. As the humanitarian sector integrates digital technologies into its operations, it faces significant cyber risks. How should the sector navigate this increasingly complex space?